"It's like starting all over again". The struggles of second-career teachers to construct professional identities in Hong Kong schools. Issue 8 (17th November 2018) - Trent, John
ABSTRACT: Educational-policy makers worldwide are concerned with finding effective strategies to recruit and retain high-quality teachers. The recruitment of second-career teachers has been seen as one means of fulfilling this aim. Against a background of calls to better understand SCTs, this article reports the results of a qualitative study investigating the experiences of six second-career teachers in Hong Kong. Based on a theoretical framework of teacher-identity construction, discourse analysis was used to explore the participants' perceptions of their professional development. In-depth interviews were conducted to gain detailed insights into how the teachers construct their identities-in-practice and identities-in-discourse within Hong Kong schools. The findings expose tensions between attempts the positioning of SCTs within dominant discourses as 'traditional' and 'conventional' teachers, for example, and the participants' self-positioning in practice as 'innovative' and 'risk-taking' teachers. Ways in SCT agency, and hence identity construction, can be facilitated through the introduction of the innovative pedagogical practices which many SCTs seek to pursue in Hong Kong schools are considered.